Immune Reconstitution Inflammatory Syndrome in Acquired Immune Deficiency Syndrome related to Cryptococcal Meningoencephalitis - Ji Young Park MD; Min Jeong Kim MD (SAGE Publishing, 2014)
Background . Highly active antiretroviral therapy (HAART) has contributed to reducing the occurrence of opportunistic infections and mortality in human immunodeficiency virus (HIV) infected patients. However, a paradoxical worsening of clinical signs and symptoms among patients during HAART may occur. Immune reconstitution inflammatory syndrome (IRIS) is described as a paradoxical deterioration of clinical status on initiation of HAART in patients with HIV infection. Case Report . We describe the case of a 41-year-old man with opportunistic cryptococcal encephalitis who exhibited neurological and radiological deterioration during the course of HAART. A diagnosis of central nervous system (CNS)-IRIS was based on a decrease of HIV-RNA viral load greater than 1 log, with an increase in CD4 + T-cell count from baseline. Conclusions . Differential diagnosis of this paradoxical deterioration in clinical and neurological status from overwhelming opportunistic infection is important; it enables an avoidance of unnecessary diagnostic procedures and proper management of this HIV-associated CNS disorder.